The Scope of Corrective Justice in Aristotle’s Ethics - Galewicz, Włodzimierz (Peitho. Examina Antiqua, 2017)
The task of corrective justice in Aristotle’s ethics is the rectification of harms or injuries resulting from voluntary or involuntary interactions between persons. However, the scope of this form of justice is not clear. In its widest conception it would include all harms done to a person against her will and without her fault. According to a narrower conception, instead, it is only an injury caused by an unjust or wrongful action that requires compensation. But in fact Aristotle distinguishes several concepts of unjust action. As a result, the narrower conception appears in various versions which are discussed in this paper.